Destabilized hypertension as a complication of therapy with nonsteroidal anti-inflammatory drugs: the importance of the problem - A. E. Karateev (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most popular tool to combat pain. Unfortunately, NSAIDs can cause various adverse reactions, among these one of the most common ones is the development or destabilization of hypertension. Controlled and observational studies have shown that the use of NSAIDs is accompanied by an average 2–3 mm Hg increase in blood pressure (BP) and persistent hypertension is noted in 2–25% of patients. In addition, NSAIDs are able to reduce the efficacy of almost all classes of antihypertensive agents with the exception of calcium channel blockers. The clinical significance of NSAID-induced hypertension is determined by a considerable increase in the risk of cardiovascular accidents, such as infarction, ischemic stroke and sudden cardiovascular death. All NSAIDs (and nonselective traditional drugs and coxibs) can negatively affect BP. Therefore, when prescribing any NSAIDs, it is necessary to take into account the presence of baseline hypertension, to monitor BP regularly, and to correct antihypertensive therapy as needed. This review deals with the key aspects of the problem with NSAID-related hypertension.